2020
DOI: 10.1007/s11673-020-09982-x
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from Corporate Influence in the Opioid Epidemic: Toward a Norm of Separation

Abstract: There is overwhelming evidence that the opioid crisis—which has cost hundreds of thousands of lives and trillions of dollars (and counting)—has been created or exacerbated by webs of influence woven by several pharmaceutical companies. These webs involve health professionals, patient advocacy groups, medical professional societies, research universities, teaching hospitals, public health agencies, policymakers, and legislators. Opioid companies built these webs as part of corporate strategies of influence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 52 publications
(55 reference statements)
0
63
0
Order By: Relevance
“…Due to historical and current interpersonal and systemic racism in the U.S., much of which is propagated at a government and policy level, racial differences in vaccine trust and lower levels of trust among African Americans may also be observed ( Quinn et al, 2016 ; Solomon and Castro, 2019 ; Feagin, 2014; Bogart et al, 2020 ; Ferdinand and Reddy, 2020). For example, an online survey on COVID-19 vaccine attitudes among U.S. adults from Marks, 2020 found that vaccine acceptability differed significantly by sociodemographic characteristics such as race ( Reiter et al, 2020 ). Indeed, it has been well-documented that African Americans report distrust in government as a salient reason for vaccine hesitancy ( Quinn et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to historical and current interpersonal and systemic racism in the U.S., much of which is propagated at a government and policy level, racial differences in vaccine trust and lower levels of trust among African Americans may also be observed ( Quinn et al, 2016 ; Solomon and Castro, 2019 ; Feagin, 2014; Bogart et al, 2020 ; Ferdinand and Reddy, 2020). For example, an online survey on COVID-19 vaccine attitudes among U.S. adults from Marks, 2020 found that vaccine acceptability differed significantly by sociodemographic characteristics such as race ( Reiter et al, 2020 ). Indeed, it has been well-documented that African Americans report distrust in government as a salient reason for vaccine hesitancy ( Quinn et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The focus on sharing one goal neglects divergence on other goals. 21,45 Similarly, manufacturers of sugary sodas have sought partnerships to promote exercise as a way to reduce weight gain rather than polices that discourage consumption of soda. 19,21,46,47 Ralston et al 37 analyzed 55 comments 48 submitted by private sector entities, NGOs, member states, UN agencies, and academic institutions in response to the draft nutrition program guidance.…”
mentioning
confidence: 99%
“…Our purpose in convening this symposium has been to introduce new ideas into this debate from a wide range of scholars with diverse backgrounds (including law, bioethics, sociology, and philosophy). Together, these articles trace COIs across different countries-from Australia to China and North America; they explore different conceptualizations of interests and COI; and they put forward new arguments for and against addressing non-financial COIs and investigate the impact of COIs on health and biomedicine (Mayes 2020 Jonathan Marks and Jing Bao's articles focus on financial COIs-with both authors calling for greater attention to institutional COIs, and the socio-political and cultural contexts in which they arise (Marks 2020;Nie et al 2020). Marks' article explores the influence of pharmaceutical companies on the formation and exacerbation of the opioid crisis in North America.…”
mentioning
confidence: 99%
“…Marks' article explores the influence of pharmaceutical companies on the formation and exacerbation of the opioid crisis in North America. Not unlike the strategies deployed by the tobacco and sugar industries, he describes the extensive web of influence-involving payments to physicians, multi-million dollar donations to universities and academic medical institutions, funding of patient advocacy groups, payments to political campaigns and public health initiatives-woven by pharmaceutical companies in order to downplay the risk of harm from opioids and to maximize company profits (Marks 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation